Penerimaan Diri pada Ibu Pasca Kematian Anak di Desa Bakungan - Indri Yani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The death of a child is one of the most profound and difficult forms of grief to deal with, especially for a mother who never imagined losing her child suddenly, where the death often triggers a prolonged grief process. To achieve self-acceptance, according to Kubler-Ross, a person will go through five stages, namely denial, anger, bargaining, depression, and acceptance. Whereas in an Islamic perspective, self-acceptance is seen through the concept of ikhlas and rida which become a guide in dealing with grief. This study aims to determine the stages of mother's self-acceptance after death, the psychological impact caused, and the Islamic perspective on self-acceptance. This study uses a qualitative approach with a phenomenological research type. This study involved three mother informants who lost their youngest child to a traffic accident. The results of this study indicate that the three informants have not achieved self-acceptance and did not fully pass through the stages of the Kubler-Ross theory, such as the first informant passing through the stages of anger, bargaining, and depression, the second informant passing through the stages of denial, anger, bargaining, and depression, and the third informant only passing through the stages of denial and depression. The psychological impacts felt by the three informants include numbness, deep sadness, longing, stress, and trauma. In an Islamic perspective, ikhlas and rida are only understood verbally by informants, which is due to the strong bond between mother and child, so that to achieve complete self-acceptance, a spiritual approach such as therapy with ustadz/ustadzah or Islamic therapists is needed, as well as family support that consistently accompanies and listens, which can help mothers accept these events with sincerity.